2017
DOI: 10.1016/j.ejvs.2017.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term Results of Chimney and Periscope Grafts in Supra-aortic Branches in High Risk Patients

Abstract: WHAT THIS PAPER ADDSThe use of chimney and periscope grafts for the treatment of aneurysms involving the supra-aortic branches is reported with mid-term follow-up. This tool uses off the shelf devices and it can be employed in the emergency setting. This single centre experience reports the use of self expandable covered stents for parallel graft construction with particular attention to a standardised technique. The limited experience and follow-up available allow the use of this technique in high risk patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 23 publications
2
30
0
2
Order By: Relevance
“…Stent graft sizing was performed using the Lachat formula. 3 The diameters of the aortic landing zone and the parallel graft were 25.5 mm and 5 mm, respectively. Therefore, we chose a 28-mm stent graft (ETBF 28-13-145 Endurant; Medtronic, Minneapolis, Minn).…”
Section: Case Reportmentioning
confidence: 95%
“…Stent graft sizing was performed using the Lachat formula. 3 The diameters of the aortic landing zone and the parallel graft were 25.5 mm and 5 mm, respectively. Therefore, we chose a 28-mm stent graft (ETBF 28-13-145 Endurant; Medtronic, Minneapolis, Minn).…”
Section: Case Reportmentioning
confidence: 95%
“…Pecoraro et al 16) reported the results of parallel graft techniques in 41 patients. About 50% (20) of the patients required zone 0 landing; however, there was no patient of Type Ia endoleak.…”
Section: Techniques To Secure Cerebral Blood Flowmentioning
confidence: 99%
“…Mid-and long-term results in large series demonstrate durability in anatomically suitable patients; however, reinterventions due to loss of proximal and distal seal compromise procedure success and stability. 2 Several endovascular techniques have been described to improve the length of seal in the proximal landing zone, such as use of chimneys and periscopes, 3,4 scallops, 5 fenestrations, 6,7 and branches. 8,9 In terms of arch and thoracic aortic anatomical parameters, angulation 10 and adequate seal zone length (>20 mm) and diameter (<40 mm) have been described as mandatory to achieve adequate seal in the proximal landing zone.…”
Section: Introductionmentioning
confidence: 99%